Building Immigration-Informed, Cross-Sector Coalitions: Findings from the Los Angeles County Health Equity for Immigrants Summit - Altaf Saadi; Mary L. Cheffers; Breena Taira; Rebecca Trotzky-Sirr; Parveen Parmar; Shamsher Samra; Janina L. Morrison; Sural Shah; Todd Schneberk (Health Equity, 2019)
In December 2017, the Los Angeles County Office of Immigrant Affairs and Board of Supervisors, alongside local health care and legal providers, convened the Health Equity for Immigrants and Families Summit to advance a vision for immigrant health. We describe the four critical concepts identified by stakeholders to address the varied needs of immigrants in an increasingly anti-immigrant political environment: (1) Recognizing immigration status as a modifiable social determinant of health; (2) Adopting the concept of ?Immigration-Informed Care? within health care institutions; (3) Establishing immigration-focused medical-legal partnerships; and (4) Building coordinated systems based on knowledge of local stakeholders, policies, and funding mechanisms.